Determinants of capital structure: A comparison between industrial and consumer sectors in China - Ying, Y.; Albaity, M.; Zainir, F. (University of Malaya, 2016)
Manuscript type: Research paper Research aims: This paper examines the effects of firm’s financial, macroeconomic, and human resource variables in determining the capital structure decisions of firms in the industrial and consumer sectors of China. It also examines the differences between the total debt and long term debt of these two sectors. Design/ Methodology/ Approach: This study analyses data from Chinese A-share firms of the consumer and industrial sectors listed in the Shanghai and Shenzen stock market exchange from the year 2008 to 2013. Dynamic panel data and the system Generalized Method of the Moments (system GMM) were employed to examine the speed of adjustment and the relationship between firm’s financial, macroeconomic, and human resource variables with two proxies of capital structure namely: total debt and long term debt. Research findings: The results indicate that the adjustment speed of capital structure decision, for both the total debt and long term debt are faster in consumer firms than they are in industrial firms. The long term debt of industrial firms is insignificantly influenced by the firm’s financial variables except for firm’s size. In consumer firms, it is noted that firm’s financial variables play an important role in explaining the leverage variations. The results also indicate that macroeconomic factors are not significant determinants of capital structure decisions, especially for industrial firms. In addition, employment size and employment in industry have significant positive impact on total debt in consumer firms while employment size and employment productivity have a negative influence on the long term debt in industrial firms. Lastly, there is a significant difference between consumer firms and industrial firms, in term of the type of debt they carry. Theoretical contributions/ Originality: This study expands on previous work done on indirect effects of sectorial and industry level factors on the relationship between leverage and firm’s specific determinants of capital structure, in developing economies. It extends the applicability of capital structure theories that are highly dependent on the types of leverage despite sector behavioural issues. Practitioner/ Policy implications: This paper provides insights on the variables which explain the level and types of leverage of Chinese firms in both the consumer and industrial sectors. Research limitations/ Implications: Future studies should consider other proxies for capital structures such as market value of total, long and short term debts. Future studies should also investigate firms in other sectors.